1997
DOI: 10.1029/97ja00440
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of tidal and planetary waves in the neutral winds and temperature observed at low‐latitude E region heights

Abstract: Abstract. We present an extensive analysis of tidal and planetary waves in the altitude range of 94 to 144 km for the January 20-30, 1993, period using the temperature and winds measured by the Arecibo incoherent scatter radar (ISR). This is the first time that simultaneous observational results for the 6-8, 12, 24 hour tides and a quasi 2-day planetary wave at E region heights have been reported at tropical latitudes. In order to derive the major oscillations from the mainly daytime data, we fill in the night… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 28 publications
8
64
0
Order By: Relevance
“…A similar analysis of the meridional wind indicates that the quasi-2-day wave is a dominant component, as reported by previous studies (Zhou et al, 1997;Jacobi et al, 2001;Huang et al, 2013b), and the quasi-27-day oscillation with maximum amplitude of about 5.6 m s −1 at 86 km is much weaker than the quasi-2-day wave. According to the spacetime series of the TIMED/SABER temperature over 20 • N, we can obtain their frequency-wavenumber spectra at 82-96 km, which shows that the strongest temperature oscillation occurs at 85 km with spectral amplitude of about 2.0 K. Figure 3 presents the normalized period-wavenumber spectrum at 85 km.…”
Section: Oscillation In Mltsupporting
confidence: 61%
“…A similar analysis of the meridional wind indicates that the quasi-2-day wave is a dominant component, as reported by previous studies (Zhou et al, 1997;Jacobi et al, 2001;Huang et al, 2013b), and the quasi-27-day oscillation with maximum amplitude of about 5.6 m s −1 at 86 km is much weaker than the quasi-2-day wave. According to the spacetime series of the TIMED/SABER temperature over 20 • N, we can obtain their frequency-wavenumber spectra at 82-96 km, which shows that the strongest temperature oscillation occurs at 85 km with spectral amplitude of about 2.0 K. Figure 3 presents the normalized period-wavenumber spectrum at 85 km.…”
Section: Oscillation In Mltsupporting
confidence: 61%
“…However, PW type oscillations are frequently observed in the thermosphere and ionosphere (Canziani, 1994;Pancheva et al, 1994). Also, vertical propagating wave events are reported in the literature at low-latitude E-region and at middle-latitude F-region (Zhou et al, 1997;Altadill and Apostolov, 1998). Although the above results are mainly for quasi-2-day oscillations, we showed the existence of upward propagating wave events with periods of about 6 days in the ionospheric F-region that were coherent with the wave activity in the MLT (Altadill and Apostolov, 2001;Altadill et al, 2001b).…”
Section: Linking Mechanisms Between the Wave Activity In The Mlt And mentioning
confidence: 98%
“…There is also observational evidence for the existence of a lowerthermospheric peak in the QTDW response. Both Ward et al (1996) and Zhou et al (1997) have observed a secondary peak in the QTDW response. Ward et al (1996) presented WINDII observations from the UARS satellite that show a QTDW response which peaks near 90 km for the meridional (zonal) component with an amplitude of 40 m s −1 (10-30 m s −1 ) at mid-southern hemisphere latitudes.…”
Section: Quasi-two-day Wave Winds and Temperaturementioning
confidence: 99%